Generals of World War II - Taylor, Mike (Edina, Minnesota ABDO publishing, 1998)
An account of the battlefield activities of German, British, American, and Russian generals during the largest war in history.
Includes index.
990L
Keywords: World War -- Biography -- Juvenile fiction -- 1939-1945; Generals -- Biography -- Juvenile fiction; World War, 1939-1945 -- Biography; Generals